2017
DOI: 10.3892/ijmm.2017.3150
|View full text |Cite
|
Sign up to set email alerts
|

TIM4-TIM1 interaction modulates Th2 pattern inflammation through enhancing SIRT1 expression

Abstract: Skewed T helper 2 (Th2)-cell polarization plays a critical role in the pathogenesis of allergic inflammations; however, the underlying mechanisms require further elucidation. The aim of the present study was to investigate the mechanisms through which the interaction between T-cell immunoglobulin and mucin domain (TIM)4 and TIM1 regulates the expression of silent information regulator 1 (SIRT1) in Th2 cells, and the role of SIRT1 in Th2-cell polarization during nasal allergic inflammation. The results demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…RNA was reverse‐transcribed into cDNA using PrimeScript First Strand cDNA Synthesis Kit (Takara, Dalian, China) according to the manufacturer's protocol, and the complementary DNA was then subjected to qPCR on the MiniOpticon™ Real‐Time PCR System (Bio‐Rad, CA, USA). The primers used in the experiments were as follows: sirt1: forward, ctgttgaccgatggactcct and reverse, gccacagcgtcatatcatcc; β‐actin: forward, gtgggaatgggtcagaagga and reverse, tcatcttttcacggttggcc were the same as described previously . The amplification protocol was performed as follows: 1 cycle at 98°C for 1 minutes, followed by 40 cycles at 98°C for 10 seconds, 56°C for 20 seconds and 72°C for 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was reverse‐transcribed into cDNA using PrimeScript First Strand cDNA Synthesis Kit (Takara, Dalian, China) according to the manufacturer's protocol, and the complementary DNA was then subjected to qPCR on the MiniOpticon™ Real‐Time PCR System (Bio‐Rad, CA, USA). The primers used in the experiments were as follows: sirt1: forward, ctgttgaccgatggactcct and reverse, gccacagcgtcatatcatcc; β‐actin: forward, gtgggaatgggtcagaagga and reverse, tcatcttttcacggttggcc were the same as described previously . The amplification protocol was performed as follows: 1 cycle at 98°C for 1 minutes, followed by 40 cycles at 98°C for 10 seconds, 56°C for 20 seconds and 72°C for 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…During allergic rhinitis inflammation, SIRT1 expression by CD4 + T cells was enhanced after interaction of TIM4 and TIM1 through promoting PI3K/Akt phosphorylation. Moreover, SIRT1 promoted the proliferation of Th2 CD4 + T cells via inhibiting Fas ligand and caspase-3 expression [28]. We found that SIRT1expression levels in nasal mucosa significantly decreased after allergic rhinitis induction in WT mice, while the SIRT1 level was much higher in HIF1a CD11c–/– mice with allergic rhinitis than in WT-AR mice.…”
Section: Discussionmentioning
confidence: 96%
“…TIMD4 is a phosphatidylserine receptor that enhances the engulfment of apoptotic cells, a primary role of macrophages in response to tissue injury. Activation of TIMD4 promotes Th1 cell apoptosis and Th2 cell proliferation (16,17), and has a prominent role in autoimmune diseases including rheumatoid arthritis and systemic lupus erythematosus (18).…”
Section: Discussionmentioning
confidence: 99%